The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12884-022-04407-6
|View full text |Cite
|
Sign up to set email alerts
|

From coercion to respectful care: women’s interactions with health care providers when planning a VBAC

Abstract: Background In many countries caesarean section rates are increasing and this impacts on choices made around mode of birth in subsequent pregnancies. Having a vaginal birth after caesarean (VBAC) can be a safe and empowering experience for women, yet most women have repeat caesareans. High caesarean section rates increase maternal and neonatal morbidity, health costs and burden on hospitals. Women can experience varied support from health care providers when planning a VBAC. The aim of this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Women who are Black, ethnic minorities, adolescents, poor, with low education levels, drug users, without housing, without prenatal care, and without a companion are more vulnerable to obstetric violence. Keedle et al 49 n = 559 Australian women who planned a vaginal birth after cesarean: n = 171 pregnant and currently planning, and n = 388 following birth Qualitative, open-ended survey/Level III The category of negative interactions between participants and healthcare providers was identified as “Fighting for my birthing rights.” Intensity varied across the sub-categories: the odds were against me, lack of belief in women birthing, and coercion. Obstetric violence was most clearly present in coercion to accept a repeat cesarean.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women who are Black, ethnic minorities, adolescents, poor, with low education levels, drug users, without housing, without prenatal care, and without a companion are more vulnerable to obstetric violence. Keedle et al 49 n = 559 Australian women who planned a vaginal birth after cesarean: n = 171 pregnant and currently planning, and n = 388 following birth Qualitative, open-ended survey/Level III The category of negative interactions between participants and healthcare providers was identified as “Fighting for my birthing rights.” Intensity varied across the sub-categories: the odds were against me, lack of belief in women birthing, and coercion. Obstetric violence was most clearly present in coercion to accept a repeat cesarean.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of obstetric violence were most clearly present in negative interactions as verbal coercion to have a repeat caesarean, threatening, and overt examples of unconsented procedures and having physical force used against the birthing person. 49 Co-researchers from Sweden found that interview participants had experienced psychological and physical abuse during childbirth that was considered obstetric violence. Results included accounts of higher-intensity experiences of obstetric violence that were compared to rape.…”
Section: Resultsmentioning
confidence: 99%
“…In the maternity environment too many women experience coercion, obstetric violence and disrespectful care and are subject to victim blaming 10 11 37. An example of this is healthcare providers dismissive attitudes to birth plans 43 44.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to assumptions about the wishes and needs of women, such as increased rates of maternal requested caesarean 7 8. International and Australian research has found women often receive mistreatment and disrespectful and abusive care from healthcare providers,9–11 particularly for women of colour 12. Internationally around a third of women identify their previous birth as a traumatic experience,13 14 which can lead to increased rates of psychosocial issues such as post-traumatic stress disorder 15 16…”
Section: Introductionmentioning
confidence: 99%
“…Women who desired a VBAC, but were unable to plan one, were less likely to experience respectful maternity care or to have autonomy in their decision making for their maternity care than women who planned a VBAC [ 9 ]. Recent studies found that individuals who reported a difference of opinion with their providers about the right care for themselves or their baby were significantly more likely to report mistreatment or to feel disrespected and coerced by their provider [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%